Psalms Old and New : Exegesis, Intertextuality, and Hermeneutics - Witherington, Ben, III, 1951- (Book collections on Project MUSE., 2017)
Reading the Book of Psalms in its original context is the crucial prerequisite for reading its citation and use in later interpretation, including the New Testament writings, argues Ben Witherington III. Here he offers pastors, teachers, and students an accessible commentary to the Psalms, as well as a reasoned consideration of how they were heard and read in early Christianity. By reading "forward and backward," Witherington advances the scholarly discussion of intertextuality and opens a new avenue for biblical theology.